International Symposium on History of Machines and Mechanisms Proceedings of HMM 2008 - Yan, Hong-Sen.; Ceccarelli, Marco. (Springer Netherlands, 2009)
The HMM 2008 International Symposium on History of Machines and Mechanisms is the third event of a series started in 2000 as the main activity of the IFToMM Permanent commission for History of MMS (Mechanism and Machine Science). The aim of History of Machines and Mechanisms conferences is to establish an international forum for presenting and discussing historical developments in the field of Mechanism and Machine Science (MMS). The subject area covers all aspects of the development of HMM, such as machines, mechanisms, kinematics, design methods, etc., that are related to people, events, objects, indeed, anything that assisted in the development of the HMM, and is presented in the form of reasoning and arguments, demonstration and identification, and description and evaluation. The HMM 2008 Proceedings contain 26 papers by authors from all over the world. The topics include historical development on mechanism and machine theory, historical figures and their works, history of mechanical engineering, ancient machines and mechanisms, reconstruction design of ancient devices, mechanism and machine design, and engineering education. This book is of interest to researchers, graduate students and engineers specializing or promoting the history of science and technology, in particular on mechanism and machine science. This book will provide the readers with extensive background information on the origin and the history of the invention of fundamental machines and mechanisms, and will undoubtedly provide further understanding and motivation for their own research and/or consultancy work.